Utilization of fruits and vegetable by-products for isolation of dietary fibres and its potential application as functional ingredients. (May 2022) - Pathania, Shivali; Kaur, Narinder
Abstract: A huge amount of waste products is being produced by the food processing industries in most countries across the globe. These huge quantities of by-products include pomace, seed, peel, stems, pulp, shells, etc. can lead to environmental pollution. Most of these industrial by-products are good sources of dietary, functional, and novel fibres. Nowadays, these dietary fibres are given great attention because of their physiological properties which are essential for human health. These waste products from fruits can further be used for the manufacturing of many functional ingredients. Highlights: The fruits and vegetable by-products are a potent source of dietary fibers. The dietary fibers find good applications in food. Dietary fibers possess various functional properties. There are many health benefits of dietary fibers.